MY BODY IS MINE CAMPAIGN RESPONDING TO POSITIVE BEAUTY TRENDS (STUDY ON UNTOUCHED BRAND THINGS) - Khalishah Irena Rifai; Noviawan Rasyid Ohorella (Universitas Gunadarma, 2022)
This study aimed to determine the impact of positive beauty trends. Things Untouched created a positive beauty campaign through brand silicone covers, the